2021
DOI: 10.1186/s12889-021-11232-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between air pollution in Lima and the high incidence of COVID-19: findings from a post hoc analysis

Abstract: Background Coronavirus disease 2019 (COVID-19) originated in the People’s Republic of China in December 2019. Thereafter, a global logarithmic expansion of cases occurred. Some countries have a higher rate of infections despite the early implementation of quarantine. Air pollution might be related to high susceptibility to the virus and associated case fatality rates (deaths/cases*100). Lima, Peru, has the second highest incidence of COVID-19 in Latin America and also has one the highest levels… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 40 publications
1
12
2
1
Order By: Relevance
“…Borro et al ( 2020 ) reported positive correlations between PM 2.5 and mortality rate ( r = 0.65, p < 0.0001) and case fatality rate ( r = 0.7, p < 0.0001), considering PM 2.5 data of days before the first reported cases in Italy. In opposite to what was found in our study, Vasquez-Apestegui et al ( 2021 ) estimated a significant association between long-term exposure to PM 2.5 and COVID-19 mortality in Peru; however, they did not observe this relationship for the lethality rate. The discrepant results between the investigations suggest that the better variable (fatality or mortality rate) to have the relationship with long-term exposure to air pollutants depends on the specific characteristics as which are the analyzed cities, socioeconomic indicators, quality of healthcare services, etc.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Borro et al ( 2020 ) reported positive correlations between PM 2.5 and mortality rate ( r = 0.65, p < 0.0001) and case fatality rate ( r = 0.7, p < 0.0001), considering PM 2.5 data of days before the first reported cases in Italy. In opposite to what was found in our study, Vasquez-Apestegui et al ( 2021 ) estimated a significant association between long-term exposure to PM 2.5 and COVID-19 mortality in Peru; however, they did not observe this relationship for the lethality rate. The discrepant results between the investigations suggest that the better variable (fatality or mortality rate) to have the relationship with long-term exposure to air pollutants depends on the specific characteristics as which are the analyzed cities, socioeconomic indicators, quality of healthcare services, etc.…”
Section: Discussioncontrasting
confidence: 99%
“…8, 2020 PM 2.5 , PM 10 , NO 2 , NO, and O 3 (past period) • In total, 1 µg/m 3 increase in NO 2 was associated with 3.1% more deaths • A total of 1 µg/m 3 increase in PM 2.5 and PM 10 was associated with 12% and 8% more cases, respectively Konstantinoudis et al ( 2021 ) England Cumulative deaths reported until Jun. 30, 2020 PM 2.5 and NO 2 (past period) • In total, 1 µg/m 3 increase in PM 2.5 and NO 2 were associated with 1.4% and 0.5% increase in mortality risk, respectively López-Feldman et al ( 2021 ) Mexico City metropolitan area Confirmed cases and deaths available on 7 Oct. 2020 PM 2.5 (past period) • PM 2.5 increases the probability of dying, even with including municipal and individual levels covariates • Its effect is monotonically increasing with age and reaches a maximum at around 80 years of age Vasquez-Apestegui et al ( 2021 ) Peru Cases and deaths occurred until Jun. 12, 2020 PM 2.5 (past period) • PM2.5 was associated with the number of cases ( β = 0.07; 95% CI : 0.034–0.107) and deaths ( β = 0.0014; 95% CI : 0.0006–0.0.0023) but not with case fatality rate Wu et al ( 2020 ) USA Death counts up to Jun.…”
Section: Introductionmentioning
confidence: 99%
“…Reforestation and the use of eco-friendly fuels are encouraged to reduce air pollution [59]. Despite efforts Ashford (109), Crowborough (108), Faversham (107), Ealing (106), London (104), Shenley (104), Cambridge (103), East Ham (103), Cranbrook (102), and Lewes (102) are most polluted cities of England [60]. United Kingdom followed the European Union laws and standards regarding air pollution as shown in Tables 4 and 5.…”
Section: United Kingdommentioning
confidence: 99%
“…Fattorini and Regoli [ 18 ] and Frontera et al [ 19 ] also showed a positive correlation in Italy, where more COVID-19 cases were found in regions with more population. Vasquez-Apestegui et al [ 20 ] showed that in Lima (Peru), the rate of COVID-19 spread was associated with higher exposure to gaseous pollutants, and Andrée [ 21 ] concluded the same in his study on the Netherlands. Furthermore, exposure to air pollution could increase vulnerability and have detrimental effects on people affected by COVID-19 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%